Malignant Catatonia: A Review for the Intensivist. (February 2023) - Connell, Jennifer; Oldham, Mark; Pandharipande, Pratik; Dittus, Robert S; Wilson, Amanda; Mart, Matthew; Heckers, Stephan; Ely, E. Wes; Wilson, Jo Ellen
Catatonia is a clinical syndrome characterized by psychomotor, neurological and behavioral changes. The clinical picture of catatonia ranges from akinetic stupor to severe motoric excitement. Catatonia can occur in the setting of a primary psychiatric condition such as bipolar disorder or secondary to a general medical illness like autoimmune encephalitis. Importantly, it can co-occur with delirium or coma. Malignant catatonia describes catatonia that presents with clinically significant autonomic abnormalities including change in temperature, blood pressure, heart rate, and respiratory rate. It is a life-threatening form of acute brain dysfunction that has several motoric manifestations and occurs secondary to a primary psychiatric condition or a medical cause. Many of the established predisposing and precipitating factors for catatonia such as exposure to neuroleptic medications or withdrawal states are common in the setting of critical illness. Catatonia typically improves with benzodiazepines and treatment of its underlying psychiatric or medical conditions, with electroconvulsive therapy reserved for catatonia refractory to benzodiazepines or for malignant catatonia. However, some forms of catatonia, such as catatonia secondary to a general medical condition or catatonia comorbid with delirium, may be less responsive to traditional treatments. Prompt recognition and treatment of catatonia are crucial because malignant catatonia may be fatal without treatment. Given the high morbidity and mortality associated with malignant catatonia, intensivists should familiarize themselves with this important and under-recognized condition.